2010
DOI: 10.1177/154193121005401206
|View full text |Cite
|
Sign up to set email alerts
|

Distractions and Interruptions in the Intensive Care Unit: A Field Observation and a Simulator Experiment

Abstract: Distractions and interruptions are frequently mentioned as sources of errors in healthcare research, and laboratory research has shown that they can disrupt cognition. However, the current evidence that distractions and interruptions cause patient harm is mixed. In two studies in an intensive care unit, we investigated whether and when distractions and interruptions might lead nurses to forget critical care tasks. Study 1 was an observational study using a mobile eye tracker. It investigated which properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…A preliminary analysis on data from four nurses was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009b) and the distribution of memory demands was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009a). In addition, a high level summary of the study has been reported in a further conference proceedings (Grundgeiger et al, 2010).Correspondence concerning this article should be addressed to Tobias Grundgeiger, Institute for Experimental Psychology, Heinrich-Heine-Universität, D-40225, Düsseldorf. E-mail: tobias.grundgeiger@uni-duesseldorf.de Journal of Experimental Psychology: Applied © 2010 American Psychological Association 2010 1076-898X/10/$12.00 DOI: 10.1037/a0021912 317 tive memory studies to explain why some anesthesiologists forgot a task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary analysis on data from four nurses was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009b) and the distribution of memory demands was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009a). In addition, a high level summary of the study has been reported in a further conference proceedings (Grundgeiger et al, 2010).Correspondence concerning this article should be addressed to Tobias Grundgeiger, Institute for Experimental Psychology, Heinrich-Heine-Universität, D-40225, Düsseldorf. E-mail: tobias.grundgeiger@uni-duesseldorf.de Journal of Experimental Psychology: Applied © 2010 American Psychological Association 2010 1076-898X/10/$12.00 DOI: 10.1037/a0021912 317 tive memory studies to explain why some anesthesiologists forgot a task.…”
mentioning
confidence: 99%
“…A preliminary analysis on data from four nurses was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009b) and the distribution of memory demands was published in a conference proceedings (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009a). In addition, a high level summary of the study has been reported in a further conference proceedings (Grundgeiger et al, 2010).…”
mentioning
confidence: 99%
“…Only 46% of students in the study had previous experience using the AED which may have increased uncertainty and stress. Another study using eye-tracking technology in nurses found that distraction led to current tasks being incomplete or missed all together 20. Distractions in simulation two in particular, could have led to students forgetting to verbalise and visualise appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…The technology has also been used in scooter riding simulations to measure hazard perception 19. One recent study related to healthcare utilised the glasses to examine distractions in nurses 20. The eye-tracking technology captured the nurses fixation on distractions and interruptions which enabled the researchers to see if it was affecting the nurses current task 20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation